Correlations of maternal neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) with birth weight. (2nd September 2017) - Akgun, Nilufer; Namli Kalem, Muberra; Yuce, Ebru; Kalem, Ziya; Aktas, Hatice
Abstract: Objective: The aim of this study is to investigate the possible correlation of hemogram parameters including neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) with birth weight and gestational week. Materials and methods: This prospective study has been conducted with 783 patients. The maternal age, parity, gestational age, type of delivery, values of complete blood count (CBC) variables and the weight of newborn were recorded. We analyzed the statistical differences between the NLR, PLR, hemoglobin (HGB), platelet distribution width (PDW), red cell distribution width (RDW), mean platelet volume (MPV), platelet, neutrophil, lymphocyte and white blood cells (WBC) in terms of the birth weight. Results: There was no statistically significant difference in the NLR in terms of the birth weight ( p  = 0.097), whereas there was a statistically significant difference in the PLR ( p  < 0.001). In correlation analyses, a linear, negative, weak and statistically significant correlation was detected between NLR and PLR with the birth weight of infant and gestational week ( p  = 0.011 and p  < 0.001, respectively). Conclusion: This prospective study is the first in the literature which investigates the correlation of NLR and PLR with the week of birth and birth weight of the infant. Our study suggested that the maternal NLR and PLR are negatively correlated with the week of birth and birth weight of the infant.